Sejarah Islam dan Politik Afghanistan - Musta'id, Ahmad (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2022)
This research is motivated by several media that present news of conflicts that often occur and are prolonged to various in the country of Afghanistan which is predominantly inhabited by Muslims. Departing from this, the author is very interested in exploring the existence of these events. This study aims to determine the history of the development of Islam and the dynamics of Islamic politics in Afghanistan. This research uses historical approach analysis. The analysis is more directed to the history of the development of Islam and political dynamics in Afghanistan. The sources in this study were obtained through several works such as articles, books, and journals. After that the data obtained is then verified, analyzed, and a conclusion is drawn. The findings of this study are that Islam has developed in Afghanistan for a long time and the turmoil of the emergence of several events such as the civil war to the emergence of the Taliban group whose movement is very massive, the emergence of several political parties that adorn democracy in Afghanistan makes political dynamics in Afghanistan very diverse.Penelitian ini dilatarbelakangi oleh beberapa media yang menyajikan  berita konflik yang sering terjadi dan berkepanjangan hingga beragam di negara Afghanistan yang mayoritas dihuni oleh orang muslim. Berangkat dari hal itu, penulis sangat tertarik untuk menelusuri adanya peristiwa tersebut. Penelitian ini bertujuan untuk mengetahui sejarah perkembangan Islam dan dinamika politik Islam di Afghanistan. Penelitian ini menggunakan analisis pendekatan sejarah. Analisis tersebut lebih mengarah kepada sejarah perkembangan Islam dan dinamika politik di Afghanistan. Sumber dalam penelitian ini diperoleh melalui beberapa karya seperti artikel, buku, dan jurnal. Setelah itu data yang diperoleh kemudian diverifikasi, dianalisis, dan diambil sebuah kesimpulan. Temuan dari penelitian ini adalah bahwasanya Islam telah berkembang lama di wilayah Afganistan dan gejolak munculnya beberapa peristiwa seperti perang saudara hingga munculnya kelompok Taliban yang pergerakannya sangat massif, munculnya beberapa partai politik yang menghiasi demokrasi di Afghanistan membuat  dinamika politik di Afghanistan sangat beragam.